2016
DOI: 10.1038/ni.3537
|View full text |Cite
|
Sign up to set email alerts
|

Foxn1 regulates key target genes essential for T cell development in postnatal thymic epithelial cells

Abstract: Thymic epithelial cell differentiation, growth and function depend on the expression of the transcription factor Foxn1, however its target genes have never been physically identified. Using novel static and inducible genetic model systems and chromatin studies, we provide now a genome wide map of direct Foxn1 target genes for postnatal thymic epithelia and define the Foxn1 binding motif. We detail the function of Foxn1 in these cells and demonstrate that in addition to the transcriptional control of genes invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
197
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(208 citation statements)
references
References 46 publications
11
197
0
Order By: Relevance
“…Furthermore, there is increasing evidence that FOXN1 is also important during thymic regeneration, as forced induction of FOXN1 is capable of reversing age-related thymic atrophy (18, 19) and recombinant FOXN1 protein can enhance T cell reconstitution after HCT (45). However, despite its importance for thymic function, it was only recently in a series of elegant studies by Hollander and colleagues that a comprehensive list of 450 high-confidence direct targets of FOXN1 were identified in cTECs (21). Importantly, this list of targets verified the four putative FOXN1 targets ( Dll4, Kitl, Ccl25 , and Cxcl12 ) that had been previously identified (20, 42).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is increasing evidence that FOXN1 is also important during thymic regeneration, as forced induction of FOXN1 is capable of reversing age-related thymic atrophy (18, 19) and recombinant FOXN1 protein can enhance T cell reconstitution after HCT (45). However, despite its importance for thymic function, it was only recently in a series of elegant studies by Hollander and colleagues that a comprehensive list of 450 high-confidence direct targets of FOXN1 were identified in cTECs (21). Importantly, this list of targets verified the four putative FOXN1 targets ( Dll4, Kitl, Ccl25 , and Cxcl12 ) that had been previously identified (20, 42).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the retinoblastoma protein (RB) family enhances thymic function and prevents ATI by controlling forkhead-box transcription factor n1 (Foxn1) expression (Garfin et al 2013). Foxn1 controls the differentiation of TECs and regulates the expression of genes implicated in the selection of thymocytes (Zuklys et al 2016). Palifermin (rhKGF) can target the RB-E2F genes in murine TECs and the RB-E2F-Foxn1 module, and thus controls the size and function of the thymus and plays a key role in thymic regeneration (Garfin et al 2014).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%
“…2). In a Foxn1-dependent manner, TECs release several chemokines, including CCL25, CCL21, and CXCL12, that allow hematopoietic progenitors to enter into the developing thymus [33,34]. These progenitors, subsequently, are committed to a T cell fate and progress through the different phases of the ontogenesis, thanks to the crosstalk with TECs and under the stimuli of TEC-derived molecules, such as the notch ligand DLL4, which, in turn, is also transcriptionally regulated by FOXN1 [35,36].…”
Section: Focus On Immunodeficiency: Foxn1 In Tecs and T Cell Developmentmentioning
confidence: 99%
“…In addition to CCL25, CXCL12, and DLL4, FOXN1 has been recently proven to promote the expression of hundreds of genes in TECs that support intrathymic T cell development through the antigen processing and presentation. In particular, it was found that the expression of Prss16 in cTECs, which encodes a thymusspecific serine protease required for CD4 lineage selection and high MHCII expression, is regulated by Foxn1 [34]. Moreover, a direct binding target of Foxn1 has been detected uniquely in cTECs, represented by a cis-regulatory element involved in the transcriptional promotion of relevant cTEC genes.…”
Section: Focus On Immunodeficiency: Foxn1 In Tecs and T Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation